THE ROLE AND IMPORTANCE OF ETHNIC CULTURE TOLERANCE IN THE EDUCATIONAL PROCESS - Tangirov Eldor Sayfullayevich (Journals Park Publishing, 2022)
In view of the students’ mentality and  of particular importance as an integral unique carrier of the sociocultural heritage, an elements of the historical and cultural. Theoretical analysis of the functions of the subject in the university educational space has revealed the potential of the possibility of partial leveling of the problems of the interaction between a teacher and students of different nationalities and ethnic groups, the organization of communication within temporary educational groups established with regard to multiple cultures by means of physical education.
Keywords: Tolerance; behavior; religious